Reactivity of sarcosine and 1,3-thiazolidine-4-carboxylic acid towards salicylaldehyde-derived alkynes and allenes - Laia, Fernanda M. Ribeiro (2013)
The reaction of sarcosine and 1,3-thiazolidine-4-carboxylic acid with salicylaldehyde-derived alkynes and allenes opened the way to new chromeno[4,3-b]pyrrole and chromeno[2,3-b]pyrrole derivatives. Tetrahydro-chromeno[4,3-b]pyrroles were obtained from the reaction of these secondary amino acids with O-propargylsalicylaldehyde. Interestingly, sarcosine reacted with ethyl 4-(2-formylphenoxy)but-2-ynoate to give a monocyclic pyrrole resulting from rearrangement of the initially formed 1,3-dipolar cycloadduct. Decarboxylative condensation of ethyl 4-(2-formylphenoxy)but-2-ynoate with 1,3-thiazolidine-4-carboxylic acid afforded in a stereoselective fashion the expected chromeno-pyrrolo[1,2-c]thiazole, which structure was unambiguously established by X-ray crystallography. However, the 1H,3H-pyrrolo[1,2-c]thiazole resulting from the opening of the pyran ring was also isolated. The reaction with O-buta-2,3-dienyl salicylaldehyde afforded 3-methylene-hexahydrochromeno[4,3-b]pyrrole. O-Allenyl salicylaldehyde reacted with sarcosine and 1,3-thiazolidine-4-carboxylic acid to give a new type of chromeno-pyrroles. A mechanism proposal for the synthesis of these chromeno[2,3-b]pyrroles has been presented.